Perceptions of Australian clients towards male radiographers working in breast imaging: Quantitative results from a pilot study. Issue 1 (February 2017) - Warren-Forward, H.M.; Mackie, B.; Alchin, M.; Mooney, T.; Fitzpatrick, P.
Abstract: Aim: Breast cancer is the second most common cause of cancer-related death in Australian women, therefore early breast cancer detection is essential. Female radiographers currently conduct breast screening in Australia; however there is a projected shortage. With many women already feeling apprehensive about attending a breast examination, possible proposals to fill this shortage must be carefully considered. Training male radiographers is one proposal however, this raises some gender concerns. This study aimed to pilot an investigation into whether it would change women's willingness to attend breast screening if conducted by a male radiographer. Method: A questionnaire completed by 146 women aged over 40 asked questions on attitude, initial reaction and how they would proceed if attended to by a male in three clinical situations (Mammography; Ultrasound and Breast Surgery). Results: The results revealed that women would have had their mammogram (90%), ultrasound (95%) and surgery (100%) conducted by a male, though some would have preferred a female for mammography (25%), ultrasound (24%) and surgery (12%). A total of 9% of women agreed to the statement 'If there were male radiographers I would not return for another screening appointment' and 9% agreed to the statement 'if I heard there could be male radiographers it would change my opinion of Breast Screening for the worse'. Conclusions: This first Australian study investigating the perceptions of women to male radiographers in the breast screening arena suggest that a mix of male and female radiographers could be accommodated and indicates the need for a larger national survey. Highlights: Over 90% would have proceeded with the examination conducted by a male radiographer. Most women were more likely to be surprised or have no reaction if examined by a male radiographer. Majority of women would "feel equally comfortable with a male practitioner as with a female". 80% disagreed to not attending an appointment "If they knew there would be a male practitioner". Data indicates that male radiographers could be carefully introduced into mammography services.